THE IMPLEMENTATION OF SCIENTIFIC APPROACH IN TEACHERS’ LESSON PLANS FOR TEACHING ENGLISH AT JUNIOR HIGH SCHOOL - Meiristiani, Noeris; Mar'atussolikha, Mar'atussolikha (LPPM Universitas Pancasakti Tegal, 2019)
Lesson plan is a plan which describes procedures and management of study in order to reach one or more basic competencies regulated in the standard of content and extended in the syllabus. The objectives of this research are 1) to analyze teachers? lesson plans in implementing scientific approach for teaching English in MTs Jatibogor, 2) to find out the problems faced by the teachers in developing English lesson plan in implementing scientific approach. This research focuses on nine lesson plans made by three teachers in different grades i.e. grades VII, VIII, and IX. This research is descriptive qualitative which uses content analysis. The research uses content analysis checklist, questionnaire, and interview. The results show that analysis of content checklist is 82.8%, which is good. The questionnaire data show that the difficulties faced by the teachers are 1) teachers still have difficulty in choosing operational verbs used to develop indicators, 2) difficulty in determining learning methods, 3) difficulty for evaluating the students? competence in accordance with authentic assessment. It is suggested that the teachers improve their understanding about Curriculum 2013 in implementing scientific approach.